Athlete`s philanthropy and social responsibility communication on social media during COVID-19 - Abuin-Penas, J.; Babiak, K.; Martinez-Patiño, M. J (Journal of Human Sport & Exercise, 2022)
As the world feels the impact of the coronavirus, the role of sport and philanthropy has merged as a venue for generating social impact and providing relief to those in need. This research focuses on the social responsibility and philanthropic mobilization of professional athletes to address urgent social needs during the COVID-19 crisis. In particular, the study focuses on the role that social media plays in the communication of these socially responsible activities developed by professional athletes. This study examined how the various ways that athletes are giving back and the messaging strategies related to the impact of COVID-19. By doing that, the authors identified three key areas: Awareness Raising and Advocacy; Calls to Action and Engagement; Information Sharing and Communication. Other relevant insights into philanthropic and social responsibility strategies and approaches were identified (e.g., direct giving, fundraising, awareness raising, mobilizing networks, or information sharing). The paper also discusses the potential responses and outcomes garnered by communicating these efforts and offers insights into how professional athletes can maximize their social impact around the world during crisis during crises such as the COVID-19.